Proceedings of the 12Th Asian Logic Conference. - Downey, R. G. (Rod G.) (World Scientific Publishing Company, 2013)
The Asian Logic Conference is one of the largest meetings, and this volume represents work presented at, and arising from the 12th meeting. It collects a number of interesting papers from experts in the field. It covers many areas of logic.